Trehalose Lipid Biosurfactant Reduces Adhesion of Microbial Pathogens to Polystyrene and Silicone Surfaces: An Experimental and Computational Approach - Janek, Tomasz; Krasowska, Anna; Czyżnikowska, Żaneta; Łukaszewicz, Marcin (Frontiers in Microbiology, 2018)
Rhodococcus fascians BD8, isolated from Arctic soil, was found to produce biosurfactant when grown on n-hexadecane as the sole carbon source. The glycolipid product was identified as the trehalose lipid with a molecular mass of 848 g mol-1. The purified biosurfactant reduced the surface tension of water from 72 to 34 mN m-1. The critical micelle concentration of trehalose lipid was 0.140 mg mL-1. To examine its potential for biomedical applications, the antimicrobial and antiadhesive activity of the biosurfactant was evaluated against several pathogenic microorganisms. Trehalose lipid showed antimicrobial activity against resistant pathogens. The largest antimicrobial activities of trehalose lipid were observed against Vibrio harveyi and Proteus vulgaris. The highest concentration tested (0.5 mg mL-1) caused a partial (11–34%) inhibition of other Gram-positive and Gram-negative bacteria and 30% inhibition of Candida albicans growth. The trehalose lipid also showed significant antiadhesive properties against all of the tested microorganisms to polystyrene surface and silicone urethral catheters. The biosurfactant showed 95% and 70% antiadhesive activity against C. albicans and Escherichia coli, respectively. Finally, the role and application of trehalose lipid as an antiadhesive compound was investigated by the modification of the polystyrene and silicone surfaces. The intermolecular interaction energy calculations were performed for investigated complexes at the density functional level of theory. The results indicate that the presence of aromatic moieties can be substantial in the stabilization of trehalose lipid-surface complexes. The antimicrobial and antiadhesive activities of trehalose lipid make them promising alternatives to synthetic surfactants in a wide range of medical applications. Based on our findings, we propose that, because of its ability to inhibit microbial colonization of polystyrene and silicone surfaces, trehalose lipid can be used as a surface coating agent